Analysis of Customers' Visual Comfort Perception and Mood for Cafes using Colored Glass Curtain - Prabu Wardono; Yuni Maharani (Journal of Visual Art and Design, 2019)
People generally prefer to work or spend leisure time under natural light rather than artificial light. Direct sunlight that enters into leisure places interrupt guests when having a meal or are enjoying the surrounding natural environment. Bamboo curtains are commonly used in Indonesia to control natural light but they do not allow people to look outside. This research was aimed at solving this problem by developing three sets of colored glass curtains"“cool colored, warm colored and combined (warm/cool colored) "“ and testing them in a real situation, which involved test subjects having a meal in a cafÃ© with a natural view, to find out which alternative had the best effect on the subjects' visual comfort and mood. Forty-two student respondents participated voluntarily in the experiment. The one way repeated measured ANOVA statistic results showed that there were significant differences in visual comfort and mood response in the same space between a number of manipulated conditions. The subjects had a significantly different visual comfort and mood response when the cool colored glass curtain was used compared to using the warm colored glass curtain or the combined glass curtain. This research concludes that bamboo shades and cool colored glass curtains are preferable to satisfy customers' visual comfort and that all the spatial conditions contribute to the customers' mood during dining.